Arterial Stiffness: A Prognostic Marker in Coronary Heart Disease. Available Methods and Clinical Application - Bonarjee, Vernon V. S. (Frontiers in Cardiovascular Medicine, 2018)
Multiple biomarkers may predict short and long-term prognosis in patients with coronary heart disease, but their impact is limited when used in addition to established risk factors such blood pressure, cholesterol levels, diabetes mellitus, smoking as well as age and sex. Arteries are an integral part of the cardiovascular (CV) system. Arterial stiffness has been shown to be a predictor of cardiovascular events and mortality independent of traditional risk factors. It has also been shown that increased arterial stiffness may predict cardiovascular events in asymptomatic individuals without overt cardiovascular disease. Measuring arterial stiffness may, therefore, identify patients at risk at an early stage. Antihypertensive treatment has been shown to reduce arterial stiffness beyond its antihypertensive effect. Arterial stiffness could, therefore, be a surrogate marker of treatment that relates to prognosis. Arterial stiffness has mostly been used in research protocols, and its use as a prognostic indicator in clinical practice is still uncommon. Several methods exist that can determine parameters related to arterial stiffness, both local and in specific artery beds such as the aorta. In this brief review we present methods to evaluate arterial stiffness, their clinical utility, limitations and the advantages of a novel method, the Cardio-Ankle Vascular Index. Easier and more reproducible methods to evaluate arterial stiffness may increase the use of parameter as a risk factor for coronary heart disease in common clinical practice.